On the Improvement of “Foreign Language + X” Multi-translation Ability of Foreign Language Majors Under the Background of New Liberal Arts - Ji, Hongqin (Pacific International Journal, 2025)
In the era of globalization, international exchanges have become increasingly frequent. During this process, the translation ability of foreign language majors has become their core competitiveness. Under the context of new liberal arts, various industries have put forward new requirements for foreign language majors, that is, possessing interdisciplinary knowledge and multi-translation ability. In this thesis, student groups from representative discipline-type institutions in Hunan Province are taken as the research subjects to conduct questionnaire surveys and interviews, exploring the current status of cultivating multi-translation ability in foreign language majors. Through statistical results, it has been found that there are common problems in current foreign language education, such as monotonous teaching content, lack of practical links, insufficient training of interdisciplinary ability, and failure to integrate modern technology. Based on the educational philosophy of new liberal arts, some suggestions have been proposed for foreign language education. It is recommended to combine specific disciplines (such as economics, law, engineering, medicine, agriculture, forestry, etc.) to build a diversified foreign language teaching and translation practice system. In addition, special emphasis has been placed on cultivating students’ cultural competence, historical competence, aesthetic competence, and logical competence through both in-class and extracurricular activities. Finally, it is also necessary to strengthen practical teaching, utilize modern information technology, and improve the teaching evaluation system, so as to enhance students’ multi-translation ability and meet the needs of society for foreign language majors.